The Inclusion of People with a Learning Disability in the Church: A Case Study - Hamilton, Ross (Journal of European Baptist Studies, 2019)
This paper is a case study of Dumbarton Baptist Church’s response to a particular ethical issue within their local Scottish community. The article will include a description of the ethical issue and the church’s response, explaining the theological and social reasons that have led the church in its thinking. Subsequently, a thorough evaluation and critical assessment of the ethical stance taken will be included, with the purpose of offering suggestions regarding ways in which such ethical challenges might be handled in the future and the impact these may have on current practices. This is intended for multiple audiences interested in theological social ethics and the involvement of those with a learning disability in church life.